2021
DOI: 10.1515/cls-2021-0024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of geometrical variations on the structural performance of shipping container panels: A parametric study towards a new alternative design

Abstract: In the field of logistics, containers are indispensable for shipments of large quantities of goods, particularly for exports and imports distributed by land, sea, or air. Therefore, a container must be able to withstand external loads so that goods can safely reach their destination. In this study, seven different models of container skins were developed: general honeycomb, cross honeycomb, square honeycomb, corrugated wall, flat, flat with a single stiffener, and flat with a cross stiffener. Testing was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…It shows that 2 mm mesh has a similar load vs. displacement curve trend compared to the experimental data. It is revealed that mesh size selection is a crucial aspect in terms of numerical modeling verification [26][27][28][29]. specimen geometries and applied load and boundary conditions are determined as shown in Figure 8.…”
Section: Benchmark Resultsmentioning
confidence: 99%
“…It shows that 2 mm mesh has a similar load vs. displacement curve trend compared to the experimental data. It is revealed that mesh size selection is a crucial aspect in terms of numerical modeling verification [26][27][28][29]. specimen geometries and applied load and boundary conditions are determined as shown in Figure 8.…”
Section: Benchmark Resultsmentioning
confidence: 99%